Analysis of Legal Responsibility for Forged Informed Consent in Emergency Medical Procedures: A Comparative Study of Indonesian Court Verdicts - Jessy Viranda; Riki Zulfiko (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Informed consent is a core ethical and legal principle in healthcare to safeguard patient autonomy. In emergencies, when consent cannot be obtained, legal limits for physicians become uncertain. An Indonesian case involving forged consent for an emergency caesarean section produced conflicting judgments between the District Court and the Supreme Court. Objective: This study analyzes regulation of informed consent in emergencies under Indonesian Law No. 17 of 2023 and compares legal reasoning of the Manado District Court and the Supreme Court. Methods: A normative legal research design was applied using comparative analysis of legal documents. Primary sources included Law No. 17 of 2023 on Health, the Indonesian Criminal Code, the Manado District Court verdict No. 90/PID.B/2011/PN.MDO, and the Supreme Court decision No. 365 K/PID/2012. Data were collected through literature review. Results: The District Court acquitted defendants by prioritizing the emergency context. Conversely, the Supreme Court convicted them, stressing criminal forgery and medical negligence contributing to patient death, supported by forensic evidence. Conclusion: The Supreme Court clarified that emergencies do not eliminate criminal liability for procedural violations such as forged consent. This decision reinforces obligations of healthcare professionals to comply with ethical and legal documentation standards during emergency care.